(untitled) - James Kirby Martin...[et al.] (New York, 1993)
The book presents U.S. history - a chronological rendering of names, dates, and facts. It deals with real people confronting real problems, with their triumphs and failures. It offers historical perspectives n lives of diverse groups of people as well as on the tumultuous affairs of nations
Keywords: united states - history